Perancangan Ulang Meja Belajar Mahasiswa Menggunakan Metode Rekayasa Nilai dan Pendekatan Ergonomi - Muhammad Yusuf; Risma Adelina Simanjuntak; Nur Rahmawati; Dian Maya Susiladewi (Jurnal Teknologi, 2021)
Yogyakarta is known as a city of students, many public and private universities. Based on this, students come from several regions to study. The learning process in higher education cannot be separated from facilities that support learning activities such as study tables and laptops. Students use laptops every day for a long time. Most students complain that the study table is not comfortable when used but it also causes students to tire more quickly. Fatigue is felt in the neck, back, legs and hands. Therefore, it is necessary to redesign the student desk to make it more ergonomic. The method used in redesigning student desks is value engineering. Function identification is performed using FAST diagrams. From the results of the identification of needs and functions, it is necessary to repair and redesign student desks. So from this study, the results of the student study table design with the addition of parts to be able to adjust the height and slope of the laptop, a place for glasses and cables, an adjustable study table height and also a footrest. Then the size of each table is adjusted to the dimensions of the Indonesian anthropometric body, the final result of this research is a more ergonomic student desk design.